Foreign Direct Investment Dynamics in Hungary - Tsaurai, Kunofiwa (Journal of Economics and Behavioral Studies, 2018)
The study discussed the dynamics of FDI in Hungary during the period from 1991 to 2015. The impact of FDI, FDI trends and determinants of FDI in Hungary were discussed. Empirical literature observed that FDI positively influenced economic growth in Hungary through boosting human capital development levels, total factor productivity, economic transformation, innovation, research and development, additional capital in the economy, modern technology, increased volume of additional capital and technology transfer. The study also revealed that most of the net FDI inflow into Hungary originated from developed countries and the least FDI net inflow came from transitional economies during the period under study. The general trend of FDI net inflow into Hungary followed a mixed pattern, with some years experiencing a positive net FDI inflow whilst other years were characterised by negative net FDI inflows. What is clear however is that FDI net inflow was consistently positive and experienced a positive growth following the integration of Hungary into the EU bloc of countries? The accession of Hungary into the EU removed barriers for the movement of capital, people, goods and services within the EU, reduced the cost of doing business and improved trade openness. These are the key locational advantages of FDI which improved FDI inflow into Hungary for a sustained period of time after the EU accession. The study also empirically tested the determinants of FDI in Hungary using the OLS multiple regression model with data ranging from 1991 to 2015. In contradiction to most previous studies on the subject matter, trade openness and financial development were found to have had a negative influence on FDI. The study also observed that inflation had a positive influence on FDI, contrary to Sayek (2009) who revealed that higher inflation levels erodes the foreign investors’ profits, thereby making the host country not an attractive investment destination. However, exchange rate, education and economic growth had a positive but non-significant impact on FDI in Hungary, consistent to both theoretical and empirical literature. The implication of the study is that the Hungarian authorities are urged to design and implement policies aimed at improving education and economic growth in order to attract more FDI. Practical steps need to be taken by the Hungarian authorities in making sure that the value of the local currency is not overvalued and that trade openness is controlled and managed so that it does not reach a point where it begins to negatively affect FDI inflows.